Case of Unilateral retinitis pigmentosa (Ukrainian Journal of Ophthalmology, 2026)
Introduction: unilateral retinitis pigmentosa is characterized by progressive destruction of photoreceptors. The disease is the result of somatic mutation during embryogenesis.Objective: presented a case of unilateral retinitis pigmentosa.Material and methods: test of visual acuity, ophthalmoscopy, field of view, optical coherence tomography, counseling by related specialists.Results: when setting the diagnosis, the presence of classic symptoms of retinitis in the affected eye, the absence of these symptoms in the second we should considered and infectious diseases should be excluded.Conclusions: the differential diagnosis for correct diagnosis and guiding further treatment should be carried out carefully.
Keywords: unilateral retinitis pigmentosa; diagnostics